2016
DOI: 10.14419/ijpt.v4i2.6578
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity of aqueous and alcoholic extracts of Glycyrrhiza glabra Linn. measured by ferric reducing antioxidant power (FRAP), ABTS bleaching assay (αTEAC), DPPH assay and peroxyl radical antioxidant assay

Abstract: The present study evaluates the in vitro antioxidant free radical scavenging capacities of aqueous and alcoholic extracts of Glycyrrhiza glabra since this medicinal plant has been traditionally used in Ayurvedic system of medicine as a tonic, rejuvenator, demulcent and expectorant. Total phenolic content of alcoholic extract and aqueous extract was found as 18.70 and 23.26 Gallic acid equivalents/mg while the total flavonoid content was assessed as 15.03 and 6.62 Quercetin equivalents/mg respectively. IC50 (µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Based on the above inhibitory activities against bacteria, it has been suggested that licorice may have a therapeutic and/or preventive capacity for oral infections (Gafner et al, 2011). Supercritical fluid extraction (SFE) is an extraction technology also applied to obtain antioxidant and antimicrobial extracts from natural sources (Fornari et al, 2012). Supercritical fluids allow high extraction rates due to their high solvation power (liquid-like density), low viscosities and high diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above inhibitory activities against bacteria, it has been suggested that licorice may have a therapeutic and/or preventive capacity for oral infections (Gafner et al, 2011). Supercritical fluid extraction (SFE) is an extraction technology also applied to obtain antioxidant and antimicrobial extracts from natural sources (Fornari et al, 2012). Supercritical fluids allow high extraction rates due to their high solvation power (liquid-like density), low viscosities and high diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…There was a concentration-dependent inhibition against hydroxyl radical exhibited by G. glabra ethanolic extract and was in the range of 35.1% [33]. The percent scavenging of ABTS and H 2 O 2 radicals was also dose dependent indicating that the root sample exhibited maximum radical scavenging activity which was supported by Mradu Gupta et al [34]. The percentage inhibition as well as the low IC 50 values of DPPH, hydroxyl, superoxide, H 2 O 2 , NO, and ABTS assay of standard ascorbic acid and methanolic extract indicates that its very high antioxidant capacity in comparison with other solvent extract.…”
Section: Discussionmentioning
confidence: 81%
“…ABTS •+ scavenging activity assay presents some advantages over DPPH scavenging test which is not convenient with water insoluble or bulky structures compounds. Therefore, the ABTS •+ scavenging activity of the extracts was also verified (Gupta et al 2016). Briefly, 7 mM of ABTS and 2.45 mM of potassium persulfate were dissolved in water, kept for 16 hours in the dark to provide ABTS •+ solution.…”
Section: Abts Cation Radical Scavenging Activitymentioning
confidence: 99%